Transcendental foundations of ethics: from metaphysics of moral subject to 'transcendentalia' as supreme values - Morozov, Andriy (Ukrainian Cultural Studies, 2022)
The article explores the transcendental conditions of the possibility of the Self as a subject of moral consciousness and ethical relations between the Self and the Other. The postmodern methodology of deconstruction of onto-theo-teleo-phallo-logo-centrism, which theoretically makes ethics impossible, is subject to criticism. The need to return to the transcendental way of philosophizing, and in particular – the metaphysics of essence, is substantiated. An ethical relationship appears when the pole of the essential is realized as the pole of the proper. The article deals with the structure of substance, which consists of matter and form, possibility and actuality. The self is a mental projection of a substance as a metaphysical principle, just as the dot we use in geometry is a graphic projection of a metaphysical principle that has no quantitative parameters (length, width, height, weight, temporal characteristics). Human substance as the whole, by definition, is greater than the mechanical sum of accidents. It acts as their inner principle of existence and organization, without which they would not have formed the unity of this particular finite human person. Anti-metaphysical philosophers criticized the concept of substance as something that is not accessible to our ordinary sensory observation. Substance is never given in sense perception alone. However, this does not prove that such a concept has no real basis. On the contrary, it convinces us that our experience consists not only of sensuously perceived, but also of spiritual-intuitive knowledge. The origin of such a concept as a substance is rooted in real personal experience. It is noted that the classical metaphysical philosophical tradition, contrary to widespread clichés, emphasizes the primacy of existence over essence. Being is the basis of being, the logical and ontological constitutive principle of its existence. Transcendentalia – unity, truth and goodness – are interpreted as value poles of attraction, or attractors. Being is understood as a sacred gift to man, which we will to know in its truth and goodness. The ethical aspect of knowledge-will is benevolence, respect for the value of being as a priori good. Benevolence is the foundation of love as a selfless attitude towards the identity and unconditional value of the spiritual and personal existence of the Other. It means substantively objective, open attitude towards the world.
Keywords: center; deconstruction; essence-substance; self; moral subject; ethical; transcendentalia; being; supreme values; objectivity; benevolence